2017
DOI: 10.1155/2017/9342789
|View full text |Cite
|
Sign up to set email alerts
|

How Arch Support Insoles Help Persons with Flatfoot on Uphill and Downhill Walking

Abstract: The main purpose of this study was to investigate the effect of arch support insoles on uphill and downhill walking of persons with flatfoot. Sixteen healthy college students with flatfoot were recruited in this study. Their heart rate, peak oxygen uptake (VO2), and median frequency (MDF) of surface electromyogram were recorded and analyzed. Nonparametric Wilcoxon signed-rank test was used for statistical analysis. The main results were as follows: (a) peak VO2 significantly decreased with arch support insoles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…The participants were instructed to walk on a treadmill with each of three slopes, a 9 degree incline (uphill walking), a -9 degree decline (downhill walking), and a level surface (level walking) [26,27] at 0.75 m/s (2.7 km/h) speed for all slopes [26][27][28]. Uphill and downhill walking were performed on different days, since walking on uphill and downhill slopes should be performed on separate days with a lapse of 24 hours to avoid interference of concentric (uphill walking) and eccentric (downhill walking) contraction [29].…”
Section: Experimental Protocolsmentioning
confidence: 99%
“…The participants were instructed to walk on a treadmill with each of three slopes, a 9 degree incline (uphill walking), a -9 degree decline (downhill walking), and a level surface (level walking) [26,27] at 0.75 m/s (2.7 km/h) speed for all slopes [26][27][28]. Uphill and downhill walking were performed on different days, since walking on uphill and downhill slopes should be performed on separate days with a lapse of 24 hours to avoid interference of concentric (uphill walking) and eccentric (downhill walking) contraction [29].…”
Section: Experimental Protocolsmentioning
confidence: 99%
“…The materials used for manufacturing orthotic insole may also be effective on flat feet function. Huang used hard arch supports walking uphill with the orthotic insole, i.e., harder, compared to walking without insoles or downhill walking [22]. Hard thermoplastic insole significantly improved flat feet function in this study; however, the mean score failed to reach 100.…”
Section: Discussionmentioning
confidence: 59%
“…For example, Banwel and Yurt assessed flat feet function after using orthotic insoles for a while [20,21]. Walking uphill was also harder for flat feet individuals using arch supports in Huang's study [22]. Kirby claimed that the medial heel skive technique is useful to control pronated feet [23].…”
Section: Introductionmentioning
confidence: 99%
“…Knowing that SSCO were designed to provide additional arch support and if we hypothesize that a flattening of the arch is associated with fatigue (i.e. loss of muscle integrity over time), this result could potentially be linked to the findings of, see [17], who reported that insoles with custom arch support help reduce the impact of fatigue during up-and downhill walking. However, none of the results presented in the current study reached statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…tibialis anterior, gastrocnemius medialis, rectus femoris and biceps femoris) decreased after wearing the custom-made orthotics. Also, see [17], studied the impact of insoles with custom arch support during uphill and downhill walking for individuals with flatfoot conditions. Their findings showed that added arch support led to a significant decrease in peak oxygen uptake (VO 2 ), as well as a potential reduction in the activity of the rectus femoris.…”
Section: Introductionmentioning
confidence: 99%